2018
DOI: 10.1063/1.5022070
|View full text |Cite
|
Sign up to set email alerts
|

The influence of alloying on the phase formation sequence of ultra-thin nickel silicide films and on the inheritance of texture

Abstract: The controlled formation of silicide materials is an ongoing challenge to facilitate the electrical contact of Si-based transistors. Due to the ongoing miniaturisation of the transistor, the silicide is trending to ever-thinner thickness's. The corresponding increase in surface-to-volume ratio emphasises the importance of low-energetic interfaces. Intriguingly, the thickness reduction of nickel silicides results in an abrupt change in phase sequence. This paper investigates the sequence of the silicides phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Thin film growth has been studied extensively for several decades. [1][2][3] One particular way of growing thin films is to anneal two elemental films (or a film and a substrate) which are in contact which each other, creating compounds at the interface during the solid-state reaction. Special attention was given to reactions between a metal layer and Si substrates, due to the role of metal silicide growth as model system for solid-state reactions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thin film growth has been studied extensively for several decades. [1][2][3] One particular way of growing thin films is to anneal two elemental films (or a film and a substrate) which are in contact which each other, creating compounds at the interface during the solid-state reaction. Special attention was given to reactions between a metal layer and Si substrates, due to the role of metal silicide growth as model system for solid-state reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to understand the effects of impurities on metal silicide formation are ongoing. 3,13,14 Surprisingly, very little is known about the effect of impurities on the SSA reaction. J.J.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of NiSi phase, via solid state reaction between Ni film (ec > 4,8nm) and Si(100), is preceded by a simultaneous formation of Ni-rich phases [1]. Recent studies have shown that the sequence of Ni-rich phases and their characteristics (texture, resistivity and interface quality) is altered by the substrate orientation [2], film thickness [1,3,4], the presence of dopants [5] and alloy elements [1,6,7]. The formation of Ni-rich phases is albeit evidenced for all preparation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…NiSi (Franciosi et al, 1982 ; Lee et al, 2000 ; Detavernier et al, 2003 ; Jin et al, 2013 ), FeSi (Damascelli et al, 1997a , b ), CoSi (Acun and Soyalp, 2012 ), and similar compounds (Kim, 2015 ) have been extensively studied with above applications in mind, and also for their various unusual physical and chemical properties (Weber et al, 2006 ; Lin et al, 2015 ; Geenen et al, 2018 ). NiSi (Connétable and Thomas, 2009 ) is structurally similar to NiGe.…”
Section: Introductionmentioning
confidence: 99%